Intracellular photocatalytic-proximity labeling for profiling protein–protein interactions in microenvironments. Issue 12 (18th January 2022) - Tsushima, Michihiko; Sato, Shinichi; Miura, Kazuki; Niwa, Tatsuya; Taguchi, Hideki; Nakamura, Hiroyuki
Abstract : Intracellular photocatalytic-proximity labeling (iPPL) was developed to profile protein–protein interactions in the microenvironment of living cells. Abstract : Intracellular photocatalytic-proximity labeling (iPPL) was developed to profile protein–protein interactions in the microenvironment of living cells. Acriflavine was found to be an efficient cell-membrane-permeable photocatalyst for introduction into the genetically HaloTag-fused protein of interest for iPPL with a radical labeling reagent, 1-methyl-4-arylurazole. iPPL was applied to the histone-associated protein H2B in HaloTag-H2B expressing HEK293FT cells. The proteins directly interacting with histones and RNA-binding proteins were selectively labeled in the intracellular environment, suggesting that the iPPL method has a smaller labeling radius ( ca. 6 nm) than the BioID and APEX methods.